G313(P) Impact of maternal and fetal inflammatory markers on neonatal and infant adiposity. (27th April 2015) - Donnelly, JMT; Lindsay, KL; Walsh, JM; Horan, M; Molloy, EJ; McAuliffe, F
Abstract : Aims: To determine the association of maternal and fetal inflammatory factors with neonatal and infant adiposity Methods: Data from 265 mother-child pairs at birth and 280 pairs at 6 months postnatal from a randomised control trial assessing the effect of a low glycaemic index diet on birth weight were analysed. Maternal TNF-alpha (TNFα) and Interleukin 6 (IL-6) were measured in early and late pregnancy and fetal levels from cord blood. Anthropometric measurements were recorded at birth and at 6 months. The sum of all skinfolds and the sum of Subscapular plus Triceps skinfolds [SS+TR] were used as markers of general adiposity and the ratio of SS/TR skinfolds as a marker of central adiposity. Results: Maternal TNFα in early pregnancy was associated with neonatal anthropometry including biceps [p = 0.048], triceps [p = 0.027] and subscapular [p = 0.002] skinfold thicknesses. TNFα in early and late pregnancy correlated with general adiposity in the neonate [SS + TR p = 0.003, p = 0.008 respectively; Sum of skinfolds p = 0.011, p = 0.002 respectively] [Table 1 ]. Maternal early and late pregnancy TNFα was also associated with 6-month-old central adiposity [SS/TR ratio p = 0.002, p = 0.030, respectively]. Fetal TNFα did not exert a significant influence on neonatal anthropometry but was associated with infant triceps skinfold at 6 months. While fetal IL-6 was associated with birth length and waist:height ratio, maternal IL-6 was not significantly associated with adiposity. On multiple linear regression analysis, TNFα contributed significantly to the majority of the final models for both neonatal and infant anthropometry, however, the models themselves were not significant. Any associations between maternal or fetal IL-6 with neonatal and infant anthropometry were no longer significant in the multiple regression models. Conclusion: Maternal TNFα significantly correlates with greater offspring adiposity at birth and 6 months and therefore may act as a potential antenatal indicator of a predisposition towards early childhood obesity.